2018
DOI: 10.5005/jp-journals-10028-1243
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification with Intraocular Implantation of Lens, Endocyclophotocoagulation, and Endoscopic-Goniosynechialysis (PIECES): A Combined Technique for the Management of Extensive Synechial Primary Angle Closure Glaucoma

Abstract: Primary angle closure glaucoma (PACG) is more blinding (1 in 4 cases) than primary open angle glaucoma (1 in 10 cases). Cataract surgery is an effective initial treatment for majority of cases of PACG. However, cataract surgery alone may not be enough to control intraocular pressure (IOP) in cases with extensive synechial angle closure glaucoma. It is reported that glaucoma drainage surgery is needed in 12% of PACG cases after cataract surgery. Some experts combine cataract surgery with either goniosynechialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 126 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Their report includes 3 patients with CACG and PAS ≥270°; the IOP was preoperatively 26, 45, and 40 mmHg, and postoperative reduction of IOP was 18, 10, and 10, respectively, at 12 months. In our study, mean preoperative IOP was 18.2 ± 6.6 and at 6 months, postoperative IOP was 12.8 ± 3.0 [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their report includes 3 patients with CACG and PAS ≥270°; the IOP was preoperatively 26, 45, and 40 mmHg, and postoperative reduction of IOP was 18, 10, and 10, respectively, at 12 months. In our study, mean preoperative IOP was 18.2 ± 6.6 and at 6 months, postoperative IOP was 12.8 ± 3.0 [9].…”
Section: Discussionmentioning
confidence: 99%
“…ECP is a complementary treatment to phacoemulsification and VGSL in patients with CACG and cataract to reduce aqueous humor production to control IOP [9, 14]. It has an acceptable safety profile compared with traditionally filtering surgery, and it could be considered a second-line treatment when iridotomy and glaucoma medications fail to control IOP [9]. In this study, we found a significant reduction in IOP and glaucoma medications; 44.8% patients did not need any glaucoma medication at 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] However, cataract extraction alone cannot address the synechial angle closure, and various studies have indicated that phacoemulsification combined with goniosynechialysis (GSL) and excisional goniotomy in PACG is a safe and more effective treatment for IOP reduction than cataract surgery alone. 9 GSL is a surgical technique that aims to strip the peripheral anterior synechia (PAS) from the angle, exposing the TM in an attempt to restore the normal aqueous outflow. The inclusion of excisional goniotomy, which involves TM strip excision using the Kahook Dual Blade (KDB, New World Medical, Rancho Cucamonga, CA) can adequately address the trabecular dysfunction caused by chronic synechiae and scarring of outflow channels.…”
Section: Introductionmentioning
confidence: 99%
“…Three quarters of cases occur in female subjects. There are 1.60 million people in Europe and 581,000 people in the USA with PACG [2].…”
Section: Introductionmentioning
confidence: 99%